Localized Corrosion Behavior of Carbon Steel as a Function of Surface Temperature and Water Condensation Rate at the Top of Oil and Gas Pipelines - Mohammed, Khalid A.; Hamad, Hazim S. (Journal of Petroleum Research and Studies, 2024)
Pitting corrosion in carbon steel can be complex and largely unpredictable, making it challenging to inhibit the propagation of pits once they have formed. The CO2 corrosion mechanism is subject to various influencing factors, including temperature, pH solution, and the duration of exposure to corrosive media. Additionally, the characteristics and structure of the protective films formed play a role in determining the likelihood of pit initiation and propagation on carbon steel surfaces. This research explores the correlation between the pitting corrosion characteristics of carbon steel and varying surface temperatures and water condensation rates in CO2-saturated environments, specifically in the top-of-line scenario. The effect of the water condensation rate (WCR) on the TLC rate was investigated at surface temperatures of 15°C, and 40°C. At a relatively low surface temperature of 15°C, Fig. (6results demonstrate that increasing the WCR above 0.712 ml/m2·s. Pitting corrosion was studied under different conditions using the surface profilometry technique. Understanding the kinetics of FeCO3 film formation, including its presence and absence, is essential in assessing the potential for localized corrosion. During a 7-day exposure period, under specific conditions of water condensation rate and steel temperature, a partially protective corrosion film developed. Nevertheless, localized corrosion was distinctly evident on the steel surface. Over time, pits appeared to be deepening, particularly at higher steel temperatures and the maximum depth was at .